Environmental Political Economy - Jennifer Clapp (Companion to Environmental Studies, 2018)
Companion to Environmental Studies presents a comprehensive and interdisciplinary overview of the key issues, debates, concepts, approaches and questions that together define environmental studies today. The intellectually wide-ranging volume covers approaches in environmental science all the way through to humanistic and post-natural perspectives on the biophysical world.